2012
DOI: 10.1002/pon.3213
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress and neurocognitive late effects in childhood cancer survivors

Abstract: Objective Surveillance of neurocognitive late effects has typically focused on the pediatric survivor alone and rarely has focused on the potential family burden. We investigated the impact of child neurocognitive effects on parenting stress, and hypothesized that parents of childhood cancer survivors with greater executive difficulties experience higher stress relative to parents of children with less adverse impact. Method Parents of 44 children who survived cancer involving CNS-directed treatments and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
1
17
1
2
Order By: Relevance
“…Such findings are in line with other recent studies suggesting that parenting stress influences child cognitive outcomes 12,13 and also provide support for our prior hypothesis that declines in cognitive functioning observed in children with retinoblastoma are at least partially mediated by parenting stress. 8 Future studies of cognitive or functional outcomes in children with cancer-both those who are expected and those who are not expected to have declines-would benefit from longitudinal designs that include indicators of parenting stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Such findings are in line with other recent studies suggesting that parenting stress influences child cognitive outcomes 12,13 and also provide support for our prior hypothesis that declines in cognitive functioning observed in children with retinoblastoma are at least partially mediated by parenting stress. 8 Future studies of cognitive or functional outcomes in children with cancer-both those who are expected and those who are not expected to have declines-would benefit from longitudinal designs that include indicators of parenting stress.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesized that non‐illness‐related factors—such as parenting stress—may have influenced outcomes, particularly given that the largest declines were observed in those children who received enucleation and no other treatment . Two papers examined the influence of parenting stress on neurocognitive outcomes in children with cancer (leukemia and lymphoma). Both papers demonstrated that parenting stress influenced neurocognitive outcomes, particularly with regard to parent‐reported functioning, with higher parenting stress associated with greater functional impairment in survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By parent report, small but statistically significant differences were identified in working memory and executive functioning. These suggest that subtle deficits can impact daily life for survivors, which may be particularly relevant in a population where higher stress levels, low education levels, and low English fluency hinder parents’ ability to assist with school work. Thus, a truly comprehensive approach for providing academic support to these survivors in the home, community, and school must take account of sociodemographic disparities …”
Section: Discussionmentioning
confidence: 99%
“…Finally, some studies described a relationship between socioeconomic status and future psychosocial consequences for the parent and the survivor child. It appears that low income and a precarious situation can lead to negative psychosocial issues such as depression, anxiety, and burnout (Patel, Wong, Cuevas, & Van Horn, 2013). no computational study (i.e., empirical models using computer simulation) has been proposed in the literature based on cognitive task performances for the participant.…”
Section: B4 Other Models For Parents Of Child Cancer Survivorsmentioning
confidence: 98%